Perubahan Karakter Agronomi Bawang Merah (Allium ascalonicum L.) Aksesi Simanindo Samosir Akibat Pemberian Berbagai Dosis Iradiasi Sinar Gamma - Jerianta Ginting; Nini Rahmawati; Mariti Mariati (Universitas Sumatera Utara, 2015)
The aim of the research was to identify the variation of agronomy characters of shallot by giving several doses of gamma rays. Research was conducted at Jl. Selamat Ketaren, Medan about 25meters above sea level started from April until July 2014. Bulbs of shallot exposed to gamma raysirradiation to several doses between 1-15 Gy (M0V1) using Co60 source and unirradiated bulbs(M0V0/control). The differencies of agronomic characters between irradiated (M) andunirradited plants (M0V) was analyze by t-test using minitab v.16. The results showed there weredifferencies between irradiated plant and unirradiated plant. Shoot emerged time of irradiated plantat doses 4-15 Gy were longer about 1,70 up to 5,36 days; shoot length and leaves number ofirradiated plant at doses 5-12 Gy in 6 weeks after planting (WAP) were shorter about 3,05 up to23,93 cm and were reduced about 1,33%; up to 79,06% compared to control. Meanwhile,harvesting age of irradiated plant at dose 4 Gy was reduced 2,05 days; weight and diameter per bulbof irradiated plant at dose 3 Gy was increased about 0,66 g and 28,59% compared to control.Keywords: shallot, irradiation, gamma rays 11V1